Becker's world of the cell - Hardin, Jeff (Pearson, 2015)
Widely praised for its strong biochemistry coverage, Becker’s World of the Cell, Eighth Edition Technology Update provides a clear, up-to-date introduction to cell biology concepts, processes, and applications. Informed by many years of teaching the introductory cell biology course, the authors have added new emphasis on modern genetic/genomic/proteomic approaches to cell biology while using clear language to ensure that students comprehend the material. Becker’s World of the Cell provides accessible and authoritative descriptions of all major principles, as well as unique scientific insights into visualization and applications of cell biology. Media icons within the text and figures call attention to an enhanced media selection—350 up-to-date animations, videos, and activities—that helps students visualize concepts